2019
DOI: 10.3390/ijms20092278
|View full text |Cite
|
Sign up to set email alerts
|

ZmASR3 from the Maize ASR Gene Family Positively Regulates Drought Tolerance in Transgenic Arabidopsis

Abstract: Abscisic acid (ABA)-, stress-, and ripening-induced (ASR) proteins are reported to be involved in drought stress responses. However, the function of maize ASR genes in enhancing drought tolerance is not known. Here, nine maize ASR members were cloned, and the molecular features of these genes were analyzed. Phenotype results of overexpression of maize ZmASR3 gene in Arabidopsis showed lower malondialdehyde (MDA) levels and higher relative water content (RWC) and proline content than the wild type under drought… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 58 publications
1
33
0
Order By: Relevance
“…These lines had lower malondialdehyde content and higher ABA and proline content improving their drought tolerance. The results thus, proved Zm ASR3 enhance drought tolerance via an ABA dependent pathway [82]. Their precise role in conferring improved tolerance to drought and salt has also been established in tomato, rice and lily [33,34,26].…”
Section: Plos Onementioning
confidence: 58%
See 1 more Smart Citation
“…These lines had lower malondialdehyde content and higher ABA and proline content improving their drought tolerance. The results thus, proved Zm ASR3 enhance drought tolerance via an ABA dependent pathway [82]. Their precise role in conferring improved tolerance to drought and salt has also been established in tomato, rice and lily [33,34,26].…”
Section: Plos Onementioning
confidence: 58%
“…Maize ASRs also have a Zn-binding domain at the N-terminal and a nuclear targeting signal with two abscissic acid/water deficit stress domains (ABA/WDS) at the C-terminal. Hybrid assays and sub-cellular fractionation studies confirmed the role of ZmASR proteins as transcription factors or molecular chaperons in different plant species [ 61 ].…”
Section: Discussionmentioning
confidence: 95%
“…Most of the ASRs in foxtail millet, maize and rice were ubiquitously expressed in all tested tissues, suggesting the wide functioning of ASRs in many development processes in cereal crops [16,37]. The TF-binding sites analysis suggested that most TaASR genes were involved in various processes during growth and development.…”
Section: Discussionmentioning
confidence: 93%
“…Also, it has been documented that overexpression of LLA23 gene in Arabidopsis conferred the cold and freezing tolerance [39]. Likewise, overexpression plantain MpASR and maize ZmASR3 in Arabidopsis, tomato SlASR1, Brachypodium distachyon BdASR1 and wheat ASR1 in tobacco all improved the tolerance to water stress [8,21,37,[40][41][42]. In addition, transgenic rice plants with overexpression of OsASR2 enhanced the tolerance to drought by targeting the GT-1 cis-element [35], while overexpression of OsASR5 enhanced the drought tolerance by regulating ABA synthesis, promoting stomatal closure, and acting as chaperone-like protein [34].…”
mentioning
confidence: 97%
See 1 more Smart Citation